PENGEMBANGAN MATERI AJAR PECAHAN DENGAN PENDEKATAN PMRI DI SD NEGERI 21 PALEMBANG - Marhamah; Zulkardi; Aisyah, Nyimas (Mathematics Education Journal, 2011)
One of mathematic lesson which is used in our daily life is fraction. Reside that fraction is Basic of mathematic learning. But it still difficult by students. Therefore, it is hended to develop the lesson by using PMRI-based to improve student‟s achievment. These research objectives are: (1) to find out the valid and practical lesson for fraction which is Developer by PMRI-based. (2) to know the potencial effect which is come up from developing the fraction lesson through students‟ achievement and their activity. Research methodology was used is development research which is included from analisis, design, evaluation and revision. In collecting the data was applied by using observation and test. Observation was done in order to see students‟ activity in process of learning by using PMRI-based and the best was used to measure their ability. The sample of this research was the third year students (35 Students) Primary Scholl 0f 21 Palembang in second semestre. The conclusions are (1) Prototype of the lesson which was Developer is valid, practical and had a potencial effect, (2) there was one ineffective aspect in process of learning that is finishing the problem solving or finding answer of the problem, comparing their solutions or discussing with friends and in asking aspect or in finding the questions/answers of friends/teacher and (3) the test result to measure students‟ ability (87,0). It showed that the level of students‟ ability is categorized as very good ability. Therefore, learning realistic mathematic can be used to improve students‟ achievement.DOI: 10.22342/jpm.5.2.584.